Prospecting the dual mode emission properties of lanthanides co-doped self-activated phosphor, Ca9Y (VO4)7: Tm3+/Yb3+ - Sharma M.; Singh P.; Singh S.K.; Singh P. (My University, 2025)
In the current work, we have examined the downconversion and upconversion luminescence behavior of Tm3+/Yb3+ co-doped. Ca9Y (VO4)7 phosphors for the first time. The phosphors sample has been successfully prepared by a solid-state reaction method. The crystallographic structure and phase purity have been certified by X-ray diffraction analysis. The upconversion (UC) spectra of Tm3+/Yb3+ co-doped Ca9Y (VO4)7 phosphor show strong blue and relatively weak red emission using excitation at 980 nm. The upconversion emission intensities of both blue and red emissions increase with an increase in pumping power. This phosphor sample also gives intense blue emission under 321 nm excitation. © 2022